The Usefulness of Readability Formulas in the Insurance Industry - Barczuk, Katarzyna (Olsztyn Economic Journal, 2015)
The aim of this paper is to characterize the most important methods which are used to determine the level of text readability. The author presents practical examples of the usage of chosen methods by foreign insurance companies. The final section of the study is completed with general conclusions relating to the application of the given solutions to the Polish insurance market.